Understanding and applying the matrix on the four levels of competences and categories of the nursing care providers - Brigita Skela-Savič; Sanela Pivač; Vesna Čuk; Branko Gabrovec (Nurses and Midwives Association of Slovenia, 2019)
Introduction: The complexity of patients' needs in today's health care calls for a revision and extension of nursing professions to ensure optimal health care outcomes. The aim of the research was to assess the understanding of the four categories of the nursing care continuum and, accordingly, four categories of nursing care providers. Methods: A descriptive, quantitative research design was employed. Participants included 365 nursing educators and nurses working in the clinical setting. The structured questionnaire used was based on the four categories of the nursing care continuum. Results: Secondary school teachers expressed significantly lower agreement with the terming of health care assistant (p < 0.001), and with the general (p < 0.001) and specific (p < 0.001) competencies of this profession, contrary to management workers (p < 0.001) and those trained in research (p = 0.030) and evidence-based care (p = 0.004) who expressed higher agreement with the competencies of health care assistants. Discussion and conclusion: The research draws attention to the issue of understanding and applying the competencies of health care assistants. In order to implement the workforce matrix of competences, the European Directive on regulated professions should be supplemented with minimum requirements for specialist knowledge and advanced practice in nursing. In addition, the competencies and minimum educational requirements for health care assistants should be defined.